Overview of exercise induced lower leg pain. Issue 2 (20th January 2011) - Allen, Mike
Abstract : Lecture 8 This paper discusses the common causes of exercise induced lower leg pain, including chronic compartment syndrome (CCS), medial tibial stress syndrome (MTSS) and chronic calf tears (CCT). The pathogenesis, clinical presentation, diagnosis and treatment of the more popular conditions are discussed. CCSs are due to an increased pressure in one or more of the four compartments of the lower leg, brought on by exercise and relieved by rest. Clinical examination of the limb is normal. Diagnosis is made by measuring the compartment pressures during exercise. Treatment is by a subcutaneous fasciotomy of the affected compartments. MTSS is thought to be due to abnormal biomechanics leading to a periostalgia of the inner tibial border both during and after exercise, with symptoms lasting up to 24–48 h postexercise. Patients always locate their pain to the inner tibial border. Examination of the limb shows the lower and often the middle inner tibial border to be tender. Diagnosis is largely clinical but may be helped by MRI scans. Treatment is initially by physiotherapy in the form of flexibility and strengthening exercises and the fitting of orthotics. If this fails then major surgery is the only other alternative. CCT occur as a result of scar tissue in the muscle or adhesions developing between the fascia and the muscle causing pain in the posterior aspect of the calf. Often there is a past history of an acute calf tear. The pain presents during a run and often the athlete will describe pain in the posterior aspect of the calf which will increase with the intensity of exercise and if they try to run through the pain they experience a tearing sensation in the calf muscle sufficient to stop them exercising and cause them to limp up to a period of 3 days. Clinical examination often reveals tenderness over the medial head of gastrocnemius. An MRI scan may or may not aide in the diagnosis. Treatment initially is in the form of physiotherapy and if this fails then operative surgery which carries an 80% success rate. Finally other rarer causes of exercise induced leg pain are discussed, namely muscle hernia, popliteal artery entrapment syndrome, nerve entrapments and metabolic disorders.